INTEGRATION OF ISLAMIC ECONOMIC PRINCIPLES IN THE GOVERNANCE OF BROILER CHICKEN FARMING ENTERPRISES - Aldi; Nuntupa; Munifa (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study examines the governance practices of broiler chicken farming enterprises and explores the extent to which Islamic economic principles are integrated into their operational management in Rejing Tiris Village, Probolinggo Regency, Indonesia. A qualitative case study design was employed, with data collected through in-depth interviews, field observations, and document analysis. The data were analyzed using a descriptive qualitative approach to capture the managerial practices and ethical dimensions of livestock farming. The findings reveal that the enterprises have implemented the core managerial functions of planning, organizing, execution, and supervision, although these practices remain largely experience-driven and informal. Effective production management, including housing preparation, feed management, animal health monitoring, and harvesting, has contributed to maintaining business continuity and operational efficiency. Furthermore, the application of Islamic economic principles is reflected in the values of honesty (ṣidq), trustworthiness (amānah), justice (ʿadl), and social responsibility, which guide farmers' daily business activities. Nevertheless, the institutionalization of these principles remains limited, as business partnerships and commercial transactions continue to rely predominantly on conventional practices without clearly defined Sharia-compliant contractual arrangements. Farmers also face significant operational challenges, including rising feed costs, market price volatility, unpredictable weather conditions, dependence on electricity, and livestock disease outbreaks. These findings suggest that strengthening managerial governance alongside a more systematic integration of Islamic economic principles is essential for enhancing the sustainability, productivity, fairness, and socio-economic value of broiler chicken farming enterprises